2017
DOI: 10.5194/tc-11-1333-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sonar gas flux estimation by bubble insonification: application to methane bubble flux from seep areas in the outer Laptev Sea

Abstract: Abstract. Sonar surveys provide an effective mechanism for mapping seabed methane flux emissions, with Arctic submerged permafrost seepage having great potential to significantly affect climate. We created in situ engineered bubble plumes from 40 m depth with fluxes spanning 0.019 to 1.1 L s −1 to derive the in situ calibration curve (Q(σ )). These nonlinear curves related flux (Q) to sonar return (σ ) for a multibeam echosounder (MBES) and a single-beam echosounder (SBES) for a range of depths. The analysis d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 58 publications
3
52
0
Order By: Relevance
“…The volumetric gas flux and methane mass flux estimated in this research are consistently lower than flux reported in previously published studies (Shakhova et al, 2010;Weber et al, 2014;Leifer et al, 2017). This is not surprising as both our estimates of volumetric gas flux and subsequent estimates of methane flux represent lower bounds of the true regional flux.…”
Section: Discussionsupporting
confidence: 66%
“…The volumetric gas flux and methane mass flux estimated in this research are consistently lower than flux reported in previously published studies (Shakhova et al, 2010;Weber et al, 2014;Leifer et al, 2017). This is not surprising as both our estimates of volumetric gas flux and subsequent estimates of methane flux represent lower bounds of the true regional flux.…”
Section: Discussionsupporting
confidence: 66%
“…Estimates of global seep emissions are based on a very limited number of measurements. Fluxes for individual marine seep vents have been reported for the Gulf of Mexico [33], offshore Norway [34,35], the North Sea [36], offshore Svalbard in the Norwegian Arctic [37], the arctic Laptev Sea [38], and numerous vents in the COP seep field [39].…”
Section: Definition Of Seepagementioning
confidence: 99%
“…Many authors have noted a relationship between seepage and geologic structures [1,2,97,107,108], including faults, diapirs, outcrops, and slumps. Near-seabed geologic structures such as authigenic carbonates [109] and low permeability sediment layers like clay [110] and ancient river valleys [38] also provide spatial control. These structures relate to low permeability migration pathways and/or allow for hydrocarbon accumulation.…”
Section: Spatial Geological Control On Seepagementioning
confidence: 99%
See 1 more Smart Citation
“…The Ob and Yenisei Rivers transport significant sediment, underlying the shallowness of the Kara Sea, with extensive proven and proposed petroleum hydrocarbon reservoirs underlying the east and southeast Kara Sea (Rekacewicz, 2005). Given the Kara Sea's shallowness, CH4 seep seabed bubbles can mostly transfer their gas directly to the atmosphere (Leifer et al, 2017;Leifer and Patro, 2002) and indirectly from wind mixing (Wanninkhof and McGillis, 1999), and also from storm sparging (Boitsov et al, 2012;Shakhova et al, 2013), which in the Arctic can extend to 100-200 m depth, i.e., most of the Kara Sea. Figure S2.…”
Section: S3 Detailed Currents and Bathymetrymentioning
confidence: 99%